Frankenstein's Children : Electricity, Exhibition, and Experiment in Early-Nineteenth-Century London - Morus, Iwan Rhys, 1964- (Book collections on Project MUSE., 1998)
During the second quarter of the nineteenth century, Londoners were enthralled by a strange fluid called electricity. In examining this period, Iwan Morus moves beyond the conventional focus on the celebrated Michael Faraday to discuss other electrical experimenters, who aspired to spectacular public displays of their discoveries. Revealing connections among such diverse fields as scientific lecturing, laboratory research, telegraphic communication, industrial electroplating, patent conventions, and innovative medical therapies, Morus also shows how electrical culture was integrated into a new machine-dominated, consumer society. He sees the history of science as part of the history of production, and emphasizes the labor and material resources needed to make electricity work.